1998
DOI: 10.1021/bi9724220
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 2-Azaanthraquinone Derivatives to DNA and Their Interference with the Activity of DNA Topoisomerases in Vitro

Abstract: We have investigated the binding ability to DNA of compounds belonging to the 2-azaanthraquinone-type structure and have examined the effect on the activity of DNA gyrase as well as on mammalian topoisomerases in vitro. Using different biophysical techniques it was found that one of these ligands, 9-((2-dimethylamino)ethyl)amino)-6-hydroxy-7-methoxy-5, 10-dihydroxybenzo[g]isoquinoline-5,10-dione (TPL-I), is an intercalating DNA binding agent, whereas the parent compound tolypocladin (TPL) and a derivative (TPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…As evidenced earlier, minor groove binders may inhibit the gyrase mediated reaction of DNA supercoiling by influencing the binding of the enzyme at or around the cleavage and religation site [9,10]. The design of an eight‐ring hairpin polyamide, which can recognize six base pairs containing four contiguous GC pairs (GGCC) identical with a strong gyrase site prompted us to examine whether this type of minor groove binder offers a basis to enhance the potency and selectivity for an anti‐topoisomerase agent.…”
Section: Resultsmentioning
confidence: 99%
“…As evidenced earlier, minor groove binders may inhibit the gyrase mediated reaction of DNA supercoiling by influencing the binding of the enzyme at or around the cleavage and religation site [9,10]. The design of an eight‐ring hairpin polyamide, which can recognize six base pairs containing four contiguous GC pairs (GGCC) identical with a strong gyrase site prompted us to examine whether this type of minor groove binder offers a basis to enhance the potency and selectivity for an anti‐topoisomerase agent.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 In particular, azaanthraquinones were tested for their ability to bind DNA and interfere with DNA polymerase activity in vitro. 9 The mode of action of azaanthraquinones was determined to be intercalation into the DNA double strand and inhibition of DNA supercoiling. 9 It has been postulated that the cytotoxicity is mediated through semiquinone radical species, which are formed during the quinone to quinol conversion and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…To extend the sequence speci®city, two or more binding agents were connected with tethers (for example, Khorlin et al, 1980;Gursky et al, 1983;Youngquist & Dervan, 1985;Lown et al, 1986Lown et al, , 1989Youngquist & Dervan, 1987;Grokhovsky & Zubarev, 1990;Singh et al, 1994;Mrksich et al, 1994;Nikolaev et al, 1996;Parks et al, 1996;White et al, 1997;Grokhovsky et al, 1998). Although most of these bis-and tri-linked polyamides did not bind to the speci®c DNA sequences, it has been reported that a few bis-linked netropsin derivatives inhibit selectively activities of topoisomerases I and II (Beerman et al, 1991;Burckhardt et al, 1997) and HIV-I reverse transcriptase (Filipowsky et al, 1996).…”
Section: Introductionmentioning
confidence: 99%